Continuous space-time crystal state driven by nonreciprocal optical forces - Raskatla, V. (2024)
We show that the continuous time crystal state can arise in an ensemble of linear oscillators from nonconservative coupling via optical radiation pressure forces. This new mechanism comprehensively explains observations of the time crystal state in an array of nanowires illuminated with light [T. Liu et al., Nat. Phys. 19, 986 (2023).NPAHAX1745-247310.1038/s41567-023-02023-5]. Being fundamentally different from regimes of nonlinear synchronization, it has relevance to a wide range of interacting many-body systems, including in the realms of chemistry, biology, weather, and nanoscale matter.